PENILAIAN KONSUMEN TERHADAP KOMPONEN 7P PRODUK â€œCHATIMEâ€ MANADO TOWN SQUARE - Melisa Verlina Seran; Leonardus Ricky Rengkung; Tommy Fredy Lolowang (Sam Ratulangi University, 2020)
This study aims to determine the consumer assessment of the 7P component of the Chatime Manado Town Square product. This research was conducted from January to March 2020. The data used in this study are primary data and secondary data. Primary data were obtained through direct interviews with 30 respondents using a questionnaire. Secondary data were obtained from books and journals related to this research topic. The results showed that the 7P component elements of the consumer products assessed, it's just that the products were always available, consumers considered disagreeing because according to consumers, Chatime Manado Town Square still often ran out of stock of certain drinks. At price and place, consumers agree. Promotion and consumer people judge neutral. In the process section, consumers agree that they agree, it's just that in the process section to get a fast product, consumers think they don't agree because according to consumers, the process to get the product has to wait in a queue and still takes quite a long time to get the product. Then on physical evidence, consumers assess agree, but in the complete room facilities section, consumers consider that they strongly disagree because according to consumers there is no wifi and consumers feel that tables and seats are still lacking.